RNA polymerase I–specific subunits promote polymerase clustering to enhance the rRNA gene transcription cycle - Albert, Benjamin (The Rockefeller University Press, 2011)
RNA polymerase I (Pol I) produces large ribosomal RNAs (rRNAs). In this study, we show that the Rpa49 and Rpa34 Pol I subunits, which do not have counterparts in Pol II and Pol III complexes, are functionally conserved using heterospecific complementation of the human and Schizosaccharomyces pombe orthologues in Saccharomyces cerevisiae. Deletion of RPA49 leads to the disappearance of nucleolar structure, but nucleolar assembly can be restored by decreasing ribosomal gene copy number from 190 to 25. Statistical analysis of Miller spreads in the absence of Rpa49 demonstrates a fourfold decrease in Pol I loading rate per gene and decreased contact between adjacent Pol I complexes. Therefore, the Rpa34 and Rpa49 Pol I–specific subunits are essential for nucleolar assembly and for the high polymerase loading rate associated with frequent contact between adjacent enzymes. Together our data suggest that localized rRNA production results in spatially constrained rRNA production, which is instrumental for nucleolar assembly.